PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAM ACHIEVEMENT DIVISION) UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI SENI RUPA SISWA KELAS VIII B SMP NEGERI 03 RENGAT - DWI RISMAWATI, Drs. Eswendi,M.Pd, Dr. Yahya, M.Pd (Serupa The Journal of Art Education, 2014)
Subjects listed in the Cultural Arts Curriculum SMP 2006 is one of the subjects that must be followed in junior high school students. This course contains the course materials: Visual arts, music, dance and theater. During the implementation of learning goes well, but specifically for students in grade 03 Rengat VIII.B State Western District of Indragiri HuluRengat found various obstacles, which the students have problems in mastering the art of learning materials, which resulted in low yields of art study materials obtained by students.Variousfactors canlead tothe study of studentsto be low, one of whichisthe learningstrategiesused by teachers. Tosolvetheproblemof learningactionusingCooperative Learning ModelSTAD(Student Teams Achievement Division).The hypothesisof thisstudyis: "The application of STAD cooperativelearning modelto improve learning outcomesartseighth grade studentsof SMP Negeri03RengatBWest. OnceimplementedTODfor twocycles, the results obtained: "Application of Cooperative Learning ModelSTADcanimprove learning outcomesVIII.Bartclass studentsof SMP Negeri03RengatWest. Ttablevaluewith31dfsignificance level of05is equal to2.042whiletcountgreaterthanthet-tablevalue, namely: (1) Differences inlearning outcomesprasiklusthefirst cycleof learningoutcomeswithtcount-14 506. (2) The difference inlearning outcomeswith thefirst cycleto thesecond cycleof learningoutcomestcount-9197; and(3) Differences inlearning outcomeswithlearning outcomesprasiklussecond cyclewithtcountof-12 870. The level ofmastery learninghas also beenhigh, the average scoreobtainedat theend of the activitywas80.78. The average scoreis alreadylarger than theKKMSubjectsArtCultureat 75.Kata kunci: Kooperatif Tipe STAD, Pembelajaran Seni Rupa.